Mortality in a cohort of Staffordshire pottery workers: follow-up to December 2008. Issue 3 (26th October 2012) - Cherry, Nicola; Harris, Jessica; McDonald, Corbett; Turner, Susan; Newman Taylor, Tony; Cullinan, Paul
Abstract : Objectives: To examine mortality from lung cancer, chronic obstructive pulmonary disease (COPD) and chronic non-malignant renal disease (cNMRD) in pottery workers exposed to silica. Methods: A cohort of Stoke-on-Trent pottery workers (N=5115), previously followed to 1992, was traced for vital status and cause of death to December 2008. Standardised mortality ratio (SMR) analyses, comparing deaths to England and Wales and Stoke-on-Trent, examined underlying cause in 1985–1992 and 1993–2008 and mentioned cause for 1993–2008. Survival analysis considered exposure duration and concentration of respirable silica for lung cancer, COPD and cNMRD, using Cox regression. Results: Excess risks of lung cancer, COPD and cNMRD were seen against both England and Wales and Stoke-on-Trent for 1985–2008. SMRs for lung cancer and COPD were lower in 1993–2008 and non-significant for lung cancer against Stoke-on-Trent in that period (SMR 1.07 95% CI 0.92 to 1.25). Exposure concentration, estimated for 1943 subjects, was related to lung cancer in smokers for early but not later deaths with mean silica concentration >200 µg/m 3 among deaths to June 1992 (HR 2.80 95% CI 1.21 to 6.50). For COPD an increasing trend with duration and (non-significantly) with mean concentration was seen for early but not later deaths in smokers. No relation was observed between estimated exposures and cNMRD. Conclusions: Excess rates of death from COPD and lung cancer were more marked in the period of the first follow-up (1985–1992) than in the second, with any relation to estimated exposure being limited to the earlier period. Conclusions about COPD and exposure were limited by an early selective destruction of files.